X-ray diffraction and thermodynamics kinetics of SiB6 under gamma irradiation dose - Mirzayev, M. N.; Jabarov, S. H.; Asgerov, E. B.; Mehdiyeva, R. N.; Thabethe, T. T.; Biira, S.; Tiep, N. V. (Silicon, 2019)
The silicide hexaboride (B6Si) was irradiated with 60Co at room temperature to study the structural changes and weight kinetics. The B6Si samples were irradiated using a gamma source with a dose rate (D) of 0.27 Gy/s. At adsorption dose range of 9.7, 48.5, 97, 145.5 and 194 kGy. The samples were analysed using X-ray diffraction (XRD) and Energy dispersive spectroscopy (EDS) to study the microstructural and composition changes. The XRD results showed the crystalline structure for the sample before and after irradiation (with gamma irradiation dose 9.7, 48.5 and 97 kGy). Amorphization of the sample began at the gamma irradiation dose of 145.5 kGy. Increase in gamma irradiation dose had an inverse effect on the activation energy and had a directly proportional effect on the lattice volume.
Keywords: X-raydiffraction; Boron compound; Silicide hexaboride; Amorphization; Crystal structure